1999
DOI: 10.1111/j.1746-1561.1999.tb02340.x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Physical Activity in Active and Low‐Active, Sixth Grade African‐American Youth

Abstract: This study compared the determinants of physical activity in active and low-active African-American sixth grade students (N = 108, 57 F, 51 M). Objective assessments of physical activity over a seven-day period were obtained using the CSA 7164 accelerometer. Students were classified as active if they exhibited three or more 20-minute bouts of moderate to vigorous physical activity over the seven-day period. Relative to low-actives, active boys reported significantly higher levels of self-efficacy, greater invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 26 publications
1
34
2
Order By: Relevance
“…Although relationships between yard presence and/or yard size and exercise equipment with physical activity are not always supported in the literature,[71,78,79] the home area, including yards and patios, was reported as the second most common location for physical activity among participating children. While many colonia houses are on relatively generous lots, often fenced or walled-in, the houses themselves are usually built piece-by-piece as the family can afford to do so (also referred to as self-built or incremental construction), usually providing limited space for active recreational endeavors indoors.…”
Section: Discussionmentioning
confidence: 99%
“…Although relationships between yard presence and/or yard size and exercise equipment with physical activity are not always supported in the literature,[71,78,79] the home area, including yards and patios, was reported as the second most common location for physical activity among participating children. While many colonia houses are on relatively generous lots, often fenced or walled-in, the houses themselves are usually built piece-by-piece as the family can afford to do so (also referred to as self-built or incremental construction), usually providing limited space for active recreational endeavors indoors.…”
Section: Discussionmentioning
confidence: 99%
“…Intermittent effects for self-efficacy were observed for increasing physical activity. Trost et al (30) examined determinants of PA in sixth-grade African American youth and reported that relative to adolescent boys who were inactive, boys who exhibited three or more 20-min bouts of MVPA a week had higher levels of self-efficacy. Relative to inactive adolescents girls, active girls reported significantly higher levels of PA self-efficacy and were significantly less likely to watch television or play video games.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of studies to date, however, have focused on non-Hispanic white populations. While a number of studies have included African American sub-samples (Hoefer, et al, 2001; McGuire, et al, 2002; Prochaska, et al, 2002; Sallis, et al, 1999), only a handful of studies have reported results for African Americans separately from other ethnic groups (Adkins, et al, 2004; Kuo, et al, 2007; Madsen, et al, 2009; McGuire, et al, 2002; Trost, et al, 1999). …”
Section: Introductionmentioning
confidence: 99%